Case Report: Kinetics and durability of humoral and cellular response of SARS-CoV-2 messenger RNA vaccine in a lung and kidney transplant recipient - Long, James; Soni, Mithil; Muranski, Pawel; Miller, Maureen J.; Conry-Cantilena, Cathleen; De Giorgi, Valeria (Frontiers in Immunology, 2023)
We present a case report of a 63-year-old female health care worker who is 15 years status post double lung transplant and six years status post living related donor kidney transplant who is healthy on a chronic immunosuppression regimen including prednisone, mycophenolate, and tacrolimus who received the SARS-CoV-2 mRNA vaccine (Pfizer-BioNTech BNT162b2) primary series and had poor initial humoral response to the COVID-19 mRNA vaccine, then demonstrated a robust, sustained immune response against S1 and S2 antigens for over seven months after receiving the recommended vaccine doses, including booster dose, without developing COVID-19 or other serious adverse events. Her immune response to vaccination indicates effective formation of anti-spike T cell memory despite chronic immunosuppression. This case report provides a comprehensive characterization of her immune response to this SARS-CoV-2 vaccination series. As vaccine effectiveness data is updated, and as better understanding of immune response including hybrid immunity emerges, these findings may reassure that recipients of SOTs may be capable of durable immune responses to emerging variants of SARS-CoV-2.